Analysis of the profile of pneumoconiosis hospitalizations from 2010 to 2020 in the Midwest Region of Brazil - Paiva, Mateus Coelho; Oliveira, Izabella Sena de; Aguiar, Yngrid Carneiro de; Barros, Natália Rodrigues Maurício (Seven Editora, 2024)
Introduction: Pneumoconiosis is the term that encompasses heterogeneous occupational interstitial lung diseases caused by the inhalation of mineral dust into the lungs. Being globally recognized as a risk to public health, knowledge and its epidemiological and economic characterization facilitate the development of occupational health policy through the elaboration of health surveillance, promotion and protection actions according to its regional distribution. Objective: To describe and analyze the profile of hospitalizations related to occupational respiratory diseases, specifically Pneumoconiosis, from 2010 to 2020 in the Midwest region. Methodology: Retrospective, descriptive and exploratory research of data collected in a virtual platform of the Department of Information Technology of SUS (DATASUS) with a focus on epidemiological data and morbidity and mortality, with the main objective of describing and analyzing these data related to occupational respiratory diseases and, specifically, Pneumoconiosis. Among the 50 selected articles, 15 were submitted to a careful analysis focusing on the objective proposed by the study. Results: When analyzing the rate of hospitalizations due to pneumoconiosis between 2009 and 2020, it was observed that 2012 was the year with the highest number of cases, followed by 2014, and, in the total of this period, 825 cases were observed in the Midwest (OC) region. The OC state with the highest number of cases was Goiás, representing about 45% of the cases, followed by the state of Mato Grosso, with approximately 39%. In addition, a predilection of males was observed, representing 60% of the cases. Conclusion: The data presented in this study establish a vast database for investigation and deeper knowledge about the occurrence of pneumoconiosis in the central region of Brazil, evidencing the importance of carrying out follow-up studies and developing public health policies related to occupational respiratory diseases. DOI:https://doi.org/10.56238/sevened2024.007-023